Spatial and Temporal Variation in Wave Overtopping Across a Coastal Structure Based on One Year of Field Observations - Jennifer Brown; Gerd Masselink; Margaret Yelland; Christopher Stokes; Timothy Poate; Robin Pascal; David Jones; John Walk; Christopher Cardwell; Barry Martin; Peter Ganderton; Julie Gregory; et al. (Journal of Marine Science and Engineering, 2025)
Coastal managers worldwide must prepare for changes in annual wave overtopping events due to climate change and sea-level rise. Research often assesses overtopping discharges by extreme events at a sea wall crest, typically using data from physical models or empirical rules based on scaled experiments. Here, we analyse a unique 1-year field dataset of coastal wave overtopping, from SW England, to determine the number of individual waves, regardless of their size, overtopping two locations across a coastal structure. The coastal conditions causing the most frequent overtopping differ from those driving it landward, complicating hazard communications for multiuse infrastructure. These data are the first field observations covering a year of tide, wave and wind conditions that cause overtopping of a vertical sea wall. Storms have a minimal (

Porcupine Abyssal Plain Sustained Observatory Monitors the Atmosphere to the Seafloor on Multidecadal Timescales - Andrew Gates; Susan Hartman; Jon Campbell; Christopher Cardwell; Jennifer Durden; Anita Flohr; Tammy Horton; Steven Lankester; Richard Lampitt; Charlotte Miskin-Hymas; Corinne Pebody; Nick Rundle; et al. (Oceanography, 2021)

Industry Partnership: Lab on Chip Chemical Sensor Technology for Ocean Observing - Matt Mowlem; Alexander Beaton; Robin Pascal; Allison Schaap; Socratis Loucaides; Sam Monk; Andrew Morris; Christopher L. Cardwell; Sara E. Fowell; Matthew D. Patey; Patricia López-García (Frontiers in Marine Science, 2021)
We introduce for the first time a new product line able to make high accuracy measurements of a number of water chemistry parameters in situ : i.e., submerged in the environment including in the deep sea (to 6,000 m). This product is based on the developments of in situ lab on chip technology at the National Oceanography Centre (NOC), and the University of Southampton and is produced under license by Clearwater Sensors Ltd., a start-up and industrial partner in bringing this technology to global availability and further developing its potential. The technology has already been deployed by the NOC, and with their partners worldwide over 200 times including to depths of ∼4,800 m, in turbid estuaries and rivers, and for up to a year in seasonally ice-covered regions of the arctic. The technology is capable of making accurate determinations of chemical and biological parameters that require reagents and which produce an electrical, absorbance, fluorescence, or luminescence signal. As such it is suitable for a wide range of environmental measurements. Whilst further parameters are in development across this partnership, Nitrate, Nitrite, Phosphate, Silicate, Iron, and pH sensors are currently available commercially. Theses sensors use microfluidics and optics combined in an optofluidic chip with electromechanical valves and pumps mounted upon it to mix water samples with reagents and measure the optical response. An overview of the sensors and the underlying components and technologies is given together with examples of deployments and integrations with observing platforms such as gliders, autonomous underwater vehicles and moorings.

The impact of oral rehabilitation coupled with healthy dietary advice on the nutritional status of adults: A systematic review and meta-analysis - Laura McGowan; Leigh-Ann McCrum; Sinead Watson; Christopher Cardwell; Bernadette McGuinness; Helen Rutherford; Victoria Paice; Ciaran Moore; Paul R. Brocklehurst; Jayne V. Woodside; Gerald McKenna (Critical Reviews in Food Science and Nutrition, 2020)

Development of custom assays for the autonomous detection and quantification of human enteric viruses in seawater using Lab on a Chip - Matthew Wilson; Julie Robidart; Catalin Balan; Christopher Cardwell; Matt Mowlem; Jonathan McQuillan (Frontiers in Marine Science, 2018)

MTHFR (C677T and A1298C) Polymorphisms and Risk of Sporadic Distal Colorectal Adenoma in the UK Flexible Sigmoidoscopy Screening Trial (United Kingdom) - Panagiota N. Mitrou; Mark A. Watson; Alexandre S. Loktionov; Christopher Cardwell; Marc J. Gunter; Wendy S. Atkin; Christopher P. Macklin; Tom Cecil; Timothy D. Bishop; John Primrose; Sheila A. Bingham (Cancer Causes & Control, 2006)